2022
DOI: 10.1021/acs.chemmater.1c04061
|View full text |Cite
|
Sign up to set email alerts
|

Phase Behavior and Superprotonic Conductivity in the System (1–x)CsH2PO4xH3PO4: Discovery of Off-Stoichiometric α-[Cs1–xHx]H2PO4

Abstract: CsH 2 PO 4 has garnered interest as a protonconducting electrolyte due to its exceptional conductivity at intermediate temperatures (228−300 °C) at which it adopts a cubic structure with a high degree of disorder. Here, through a study of mixtures of CsH 2 PO 4 (CDP) and CsH 5 (PO 4 ) 2 , the cubic phase was discovered to form solid solutions of composition [Cs 1−x H x ]H 2 PO 4 , with x extending to at least 2/9. A phase diagram of the composition space (1−x)CsH 2 PO 4 − xH 3 PO 4 , 0 ≤ x ≤ 2/9 was developed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 27 publications
(51 reference statements)
0
7
0
Order By: Relevance
“…Furthermore, the compound Ba 2 KH(PO 4 ) 2 , despite being essentially isostructural to superprotonic Rb 3 H(SeO 4 ) 2 , does not have particularly high conductivity. 19 While these lines of investigation have not proven fruitful, a recent, promising approach to the development of new phosphate based superprotonic electrolytes based on ‘off-stoichiometric’ compositions 20 or ‘heterogeneous doping’ 21 has emerged. Here, one pursues materials in which the cation:polyanion atomic ratio deviates from the canonical values of 1 : 1 as found in the x CsHSO 4 – (1 − x )CsH 2 PO 4 series of compounds 12,22–24 and of 3 : 2 as found in A 3 H(XO 4 ) 2 (A = Cs, Rb, NH 4 , K; X = S, Se) 11 and A 3 H 3 (PO 4 ) 2 20 compounds.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the compound Ba 2 KH(PO 4 ) 2 , despite being essentially isostructural to superprotonic Rb 3 H(SeO 4 ) 2 , does not have particularly high conductivity. 19 While these lines of investigation have not proven fruitful, a recent, promising approach to the development of new phosphate based superprotonic electrolytes based on ‘off-stoichiometric’ compositions 20 or ‘heterogeneous doping’ 21 has emerged. Here, one pursues materials in which the cation:polyanion atomic ratio deviates from the canonical values of 1 : 1 as found in the x CsHSO 4 – (1 − x )CsH 2 PO 4 series of compounds 12,22–24 and of 3 : 2 as found in A 3 H(XO 4 ) 2 (A = Cs, Rb, NH 4 , K; X = S, Se) 11 and A 3 H 3 (PO 4 ) 2 20 compounds.…”
Section: Introductionmentioning
confidence: 99%
“…25 Rather remarkably, the CsH 2 PO 4 and Cs 7 (H 4 PO 4 )(H 2 PO 4 ) 8 compounds exhibit eutectoid behavior, forming a non-stoichiometric cubic superprotonic phase of composition stoichiometry Cs 1− x H 2+ x PO 4 over a wide range in x . 20 In parallel, Gaydamaka et al have pursued an analogous study of the RbH 2 PO 4 – Rb 2 HPO 4 system. 26 These authors have reported that the compound Rb 5 H 7 (PO 4 ) 4 , with a cation : polyanion ratio of 5 : 4, undergoes a superprotonic transition at ∼237 °C at which the conductivity rises from ∼10 −5 to ∼10 −2 S cm −1 , and the activation energy for proton transport becomes ∼0.9 eV.…”
Section: Introductionmentioning
confidence: 99%
“…Solids with mobile ions, such as H + , Li + , Na + , Ag + , F – , and O 2– , play a pivotal role in materials science for a range of applications. In particular, they are needed to realize all-solid-state lithium and sodium batteries and to develop oxide fuel cells. , The search for proton conductors ,,, to develop proton conducting fuel cells has also reached a rather high level. Classical proton conducting ceramics ,, include oxides such as alkaline earth cerates and zirconate perovskites based on acceptor-doped SrCeO 3 , BaCeO 3 , SrZrO 3 , and BaZrO 3 and other compounds such as CsH 2 PO 4 . , Usually, protons are incorporated in, e.g., BaZrO 3 by treatment with water vapor or H 2 gas. Recently, it has been shown that the exact proton concentration in Y-doped BaZrO 3 sensitively affects H + conductivities involving nanoscale percolation pathways with low dimensionality …”
Section: Introductionmentioning
confidence: 99%
“…19 From mixtures of CDP and CsH 5 (PO 4 ) 2 , Wang et al synthesized new proton conducting phases (in particular the compound CPP) with increased proton concentrations compared to CDP. 6,20 In addition to increasing the proton concentration, the partial replacement of Cs ions with H 4 PO 4 + also significantly affects the topology of the hydrogen bond network in CDP. A fluctuating and strong hydrogen bond network is a fundamental prerequisite for efficient Grotthuss-like proton transfer.…”
mentioning
confidence: 99%
“…This strategy has already been tested by doping CDP with phosphoric acid, but this direct approach for incorporating excess protons did not significantly change the properties of the superconducting phase of CDP . From mixtures of CDP and CsH 5 (PO 4 ) 2 , Wang et al synthesized new proton conducting phases (in particular the compound CPP) with increased proton concentrations compared to CDP. , In addition to increasing the proton concentration, the partial replacement of Cs ions with H 4 PO 4 + also significantly affects the topology of the hydrogen bond network in CDP. A fluctuating and strong hydrogen bond network is a fundamental prerequisite for efficient Grotthuss-like proton transfer. Therefore, this type of chemical modification of CDP represents a promising approach for fine-tuning the proton conductivity in this compound.…”
mentioning
confidence: 99%